Extrapolation Errors in Liu et al.’s CAM Integrative Review of Health Care Professionals in New Zealand - McDowell, JM; Kohut, SH; Betts, D (Springer Science and Business Media LLC, 2024)
This letter is to highlight errors made by Liu et al. in their 2020 paper in BMC Complementary Medicine and Therapies, “Complementary and alternative medicine—practice, attitudes, and knowledge among healthcare professionals in New Zealand: an integrative review”. Substantial errors in their citation of the recent research and methodology by McDowell, Kohut & Betts (2019) pertaining to the practice of acupuncture in New Zealand by physiotherapists are presented. The actual results of McDowell et al.’s work and the true state of acupuncture use by their sample group is reported.
Keywords: Acupuncture; Error; Extrapolation; Physiotherapy; Safety; Survey; 42 Health Sciences; 4208 Traditional, Complementary and Integrative Medicine; Mind and Body; Complementary and Integrative Health; Generic health relevance; 3 Good Health and Well Being; New Zealand; Humans; Health Personnel; Complementary Therapies; Acupuncture Therapy; Health Knowledge, Attitudes, Practice; Attitude of Health Personnel; New Zealand; Humans; Health Personnel; Complementary Therapies; Acupuncture Therapy; Health Knowledge, Attitudes, Practice; Attitude of Health Personnel